Greenhouse Gas Emissions and Health in the Countries of the European Union - Beata Gavurova; Martin Rigelsky; Viera Ivankova (Frontiers Media S.A., 2021)
In the current era of globalization, a clean environment remains a crucial factor for the health of the population. Thus, improving air quality is a major focus of environmental policies, as it affects all aspects of nature, including humans. For these reasons, it is appropriate to take into account the health risks posed by greenhouse gas (GHG) emissions released into the atmosphere. With regard to global GHG emissions, there are concerns about the loss of protection of the ozone layer and it is very likely that climate change can be expected, which multiplies the environmental threat and has potentially serious global consequences. In this regard, it is important to pay increased attention to emissions that enter the atmosphere, which include countless toxic substances. The aim of this study was to examine the associations between selected GHG emissions and the health of the European Union (EU) population represented by disability-adjusted life years (DALYs). This aim was achieved using several analytical procedures (descriptive analysis, correlation analysis, cluster analysis, and panel regression analysis), which included five environmental variables (carbon dioxide (CO2), methane (CH4) in CO2 equivalent, nitrous oxide (N2O) in CO2 equivalent, hydrofluorocarbons (HFC) in CO2 equivalent, sulfur hexafluoride (SF6) in CO2 equivalent) and one health variable (DALYs). An emphasis was placed on the use of quantitative methods. The results showed that CO2 emissions have a dominant position among selected GHG emissions. The revealed positive link between CO2 and DALYs indicated that a decrease in CO2 may be associated with a decrease in DALYs, but it is also true that this cannot be done without reducing emissions of other combustion products. In terms of CO2, the least positive scores were observed in Luxembourg and Estonia. Germany had the lowest score of DALYs, representing the most positive health outcome in the EU. In terms of total GHG emissions, Ireland and Luxembourg were considered to be less positive countries compared to the other analyzed countries. Countries should focus on reducing GHG emissions in general, but from a health point of view, reducing CO2 emissions seems to be the most beneficial.